PENGARUH MEDIA INTERAKTIF RIMBA RAJA TERHADAP KEMAMPUAN MEMBACA DAN MOTIVASI BELAJAR AKSARA JAWA KELAS IV SDN JATISARI - Putri, Aprilia Kurnia Putri; Sukasih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted to determine the effect of using Rimba Raja interactive learning media on reading ability and the presence of motivation to learn Javanese script in elementary schools. This type of research is Quasi Experimental Design with a Pretest-Posttest Non-Equivalent Control Group Design. The population of this research was all students in class IV of Jatisari State Elementary School, totaling 84 students, with a research sample of 28 class 4a students and 28 class 4c students of Jatisari State Elementary School. Both classes have the same abilities before being given treatment. The instruments used in this research were tests and motivation questionnaires. Based on the results of the hypothesis test on the influence of reading ability and motivation using the independent sample t-test, a significance value of 0.000 <0.05 was obtained and showed that Ha was accepted and H0 was rejected. These results prove that the Rimba Raja interactive learning media has an effect on reading ability and motivation to learn Javanese script in class IV Javanese language subjects at Jatisari State Elementary School.